Entrepreneurship Capital and Performance of Social Forestry Entrepreneurship Group - Kusuma, Gita Ardia; Suharjito, Didik; Trison, Soni (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
It is important to explain community forestry entrepreneurship in the context of community forest management, which continues to develop as social entrepreneurship that can increase sources of livelihood and environmental benefits. This study adapted the concept of community capital to explain the level of entrepreneurial capital and its influence on the performance of the Social Forestry Entrepreneurial Group (SFEG) through a quantitative approach by collecting data from Focus Group Discussions (FGD), interviews, observations, and literature studies. Data analysis was used with scoring, categorizing, and multiple regression analysis. The results of this study reveal the level of entrepreneurial capital in SFEG in the low to very high category is directly proportional to the simultaneous effect on performance. Natural capital, finance capital, and political capital significantly influence socioeconomic and environmental performance; political capital increases social capital, physical capital, and human capital. SFEG based on forest resource commodities as a source of livelihood needs to get attention, including increasing human capital in the form of intensive skills through a mentoring process by officers and easy access to funding sources throughgovernment policies.